Patients without records and records without patients: review of patient records in primary care and implications for surveillance of antibiotic prescribing in rural China - Rachel Kwiatkowska; Xingrong Shen; Manman Lu; Jing Cheng; Matthew Hickman; Helen Lambert; Debin Wang; Isabel Oliver (BMC, 2020)
Abstract Background We need to monitor patterns of antibiotic prescribing in order to develop and evaluate antibiotic stewardship interventions in rural China. As part of a multidisciplinary study of antibiotic use in Anhui Province we assessed the validity of electronic records (e-records) as a source of surveillance data. Methods One township healthcare centre and one village clinic were selected in each of three different counties. Patients with symptoms of Upper Respiratory Tract Infection (URTI), exacerbation of Chronic Obstructive Pulmonary Disease (COPD) or Urinary Tract Infection (UTI) were recruited consecutively. Researchers observed and documented clinic consultations and interviewed each of the study participants. E-records were compared to clinic observations and patient interviews. Results A total of 1030 patients were observed in clinic. Antibiotics were prescribed in 917 (89%) of consultations. E-records were created only for individuals with health insurance, with considerable between-site variation in completeness (0 to 98.7% of clinic consultations) and in the timing of documentation (within-consultation up to weeks afterwards). E-record accuracy was better in relation to antibiotics (82.8% of e-records accurately recorded what was prescribed in clinic) than for diagnosis and symptoms (45.0 and 1.1% accuracy). Only 31 participants (3.0%) presented with UTI symptoms. Conclusions We have confirmed very high rates of outpatient antibiotic prescribing in rural Anhui province. E-records could provide useful information to inform stewardship interventions, however they may be inaccurate and/or biased. Public Health authorities should focus on improving technical infrastructure and record-keeping culture in outpatient settings. Further research is needed into community treatment of UTIs.